A review of the catalytic hydrogenation of carbon dioxide into value-added hydrocarbons - Yang, Haiyan; Zhang, Chen; Gao, Peng; Wang, Hui; Li, Xiaopeng; Zhong, Liangshu; Wei, Wei; Sun, Yuhan (Catalysis science & technology, 2017)
Chemical utilization of CO 2 to chemicals and fuels is very attractive because it can not only alleviate global warming caused by increasing atmospheric CO 2 concentration but also offer a solution to replace dwindling fossil fuels. Hydrogen is a high-energy material and can be used as the reagent for CO 2 transformation. Moreover, when hydrogen originates directly from renewable energy, CO 2 hydrogenation can also provide an important approach for dealing with the intermittence of renewable sources by storing energy in chemicals and fuels. Therefore, much attention has been paid to CO 2 hydrogenation to various value-added hydrocarbons, such as lower olefins, liquefied petroleum gas, gasoline, aromatics and so on. The focus of this perspective article is on the indirect and direct routes for production of hydrocarbons from CO 2 hydrogenation and recent developments in catalyst design, catalytic performance and reaction mechanism. In addition, a brief overview on CO 2 hydrogenation to methanol is given, which is a critical process in the indirect route involving conversion of CO 2 into methanol and subsequent transformation into hydrocarbons. We also provide an overview of the challenges in and opportunities for future research associated with CO 2 hydrogenation to value-added hydrocarbons. We review the indirect and direct routes for CO 2 hydrogenation to hydrocarbons and recent developments in catalyst design, performance and mechanism.